Cognition in older adults with healthy aging: analysis of the Mexican Health and Aging Study 2012–2015 - Yeverino-Castro, Sara G.; Garza-Guerra, José D.; Aguilar-Díaz, Gabriela E.; González-Galván, Célica R.; Salinas-Martínez, Ricardo; Morales-Delgado, Rocío (Frontiers in Medicine, 2023)
Introduction: Maintaining older adults’ health and well-being can be achieved through the optimization of physical and mental health, while preserving independence, social participation, and quality of life. Cognitive change has been described as a normal process of aging and it involves domains such as processing speed, attention, memory, language, visuospatial abilities, and executive functioning, among others. Objective: To describe cognitive changes in older adults with healthy aging. Methods: This is a study that involved data from 14,893 and 14,154 individuals aged >60 years or older from the 2012 and 2015 waves, respectively, who participated in the Mexican Health and Aging Study (MHAS). Participants with healthy aging were identified and described in the MHAS-2012 wave and followed to 2015. Eight cognitive domains evaluated in the Cross-Cultural Cognitive Evaluation (CCCE,) as well as sociodemographic and health characteristics, were described. Criteria for healthy aging involved the following: CCCE ≥ -1.5 standard deviations above the mean on reference norms, independence on basic and instrumental activities of daily living, self-reported “life close to ideal”, and preserved functional and social performance. Results: From a total of n= 9,160 older adults from the MHAS-2012 wave, n=1,080 (11.8%) had healthy aging. In the healthy aging group, the median age was 67 years (IQR: 63-73), 58.1% were female and the median for education was 6 (IQR: 3-8) years. The mean CCCE score was 57 (SD: 16.9) points. In the MHAS-2012 cross-sectional analysis, except for orientation, visuospatial abilities, and verbal fluency, all cognitive domain scores were lower with passing age. When comparing cognitive domain scores in the 225 older adults identified with healthy aging between the 2012 and 2015 MHAS waves, there were almost no observable differences. Conclusion: In the cross-sectional analysis, Mexican adults with healthy aging had lower scores in the verbal learning memory, visual scanning, numeracy, visual memory, and verbal recall domains’, as well as lower global cognitive scores in the higher age groups. There were no cognitive changes in the 3-year follow-up, except for a lower gradient of scores in the verbal recall memory domain. Longer prospective studies are needed to characterize greater cognitive changes.